The Partial Duplication of the 5′ Segment of KMT2A Revealed KMT2A-MLLT10 Rearrangement in a Boy with Acute Myeloid Leukemia - Hiroko Fukushima; Toru Nanmoku; Sho Hosaka; Yuni Yamaki; Nobutaka Kiyokawa; Takashi Fukushima; Ryo Sumazaki (Case Reports in Pediatrics)
The duplication of 5′ segment of KMT2A is a rare molecular event in childhood leukemia, and the influence on prognosis is unknown. Here, we report on a boy who developed acute monocytic leukemia. Fluorescence in situ hybridization revealed the duplication of the 5′ segment with 2 normal alleles at KMT2A which was eventually found to be fused with MLLT10. Chemotherapy promptly induced the first complete remission in the patient at our facility, and the patient remained in first complete remission with negative minimal residual disease at 3.5 years from diagnosis. Our case is similar to two previously reported patients who had partial duplication of the 5′ segment of KMT2A with a KMT2A-MLLT10 rearrangement. Further studies and experience with this cryptic translocation may shed more light on the management of acute myeloid leukemia.